Linkage between Job Satisfaction, Democratic Leadership Style and the Organizational Commitment of Employees of Privates of Bank in Nepal (Researcher: A Research Journal of Culture and Society, 2020)
This study investigated the effect of job satisfaction and perceived democratic leadership style of the managers on the organizational commitment of the employees working in the private banks in Nepal. The population in this study was all employees working in the private banks in Nepal. A hybrid instrument, which comprised pre-tested instruments, was used to collect the data. The analytical method used to test the hypothesis of the research was multiple regression analysis. Statistical Package for Social Science (SPSS), version 25, was used for analyzing the data. The study's findings- job satisfaction of the employees and their perception of the democratic leadership style of their managers, had a significant positive impact on their organizational commitment. This study's originality is that this study shows how the employees' perception of their manager's democratic leadership style and their job satisfaction affect their organizational commitment to the Nepalese context.